The grand design - Hawking, Stephen; Mlodinow, Leonard, 1954- (London : Bantam Books/Transworld Publishers, 2011)
Along with Caltech physicist Mlodinow (The Drunkard's Walk), University of Cambridge cosmologist Hawking (A Brief History of Time) deftly mixes cutting-edge physics to answer three key questions-- Why is there something rather than nothing? Why do we exist? Why this particular set of laws and not some other?-- and explains that scientists are approaching what is called'M-theory,' a collection of overlapping theories (including string theory) that fill in many (but not all) the blank spots in quantum physics. This collection is known as the'Grand Unified Field Theories.'
The mystery of being -- The rule of law -- What is reality? -- Alternative histories -- The theory of everything -- Choosing our universe -- The apparent miracle -- The grand design.
Includes index.
Previous publication : New York : Bantam Books , 2010.
Koleksi sumbangan : Dr. Syaidatun Nazirah Abu Zahrin.
Keywords: Unified field theories -- Popular works; Superstring theories -- Popular works; Mathematical physics -- Popular works